Mononuclear cell collection for extracorporeal photopheresis by using the "off‐line" system: A comparative study between COBE Spectra and Spectra Optia devices. Issue 4 (14th December 2018) - Pascual, Cristina; González‐Arias, Elena; Pérez‐Corral, Ana María; Bailén, Rebeca; Gayoso, Jorge; Besson, Nelly; Serrano, David; Kwon, Mi; Anguita, Javier; Díez‐Martín, José Luis
Abstract : Background: Extracorporeal photopheresis (ECP) is an efficient and established therapy to treat acute and chronic graft vs host disease (GVHD). Using an "off‐line " method, the first step (mononuclear cell [MNC] collection) is decisive, as long as a high MNC yield and purity in the collected product is desirable. Two "off‐line " devices were compared: the COBE Spectra and the Spectra Optia (Terumo BCT), using both continuous and intermittent protocols. Patients and methods: Twelve patients with GvHD (7 acute/5 chronic) were enrolled between June 2014 and May 2015 and were alternatively assigned for each procedure to either the COBE Spectra or the Spectra Optia cell separator. Patients characteristics and procedure/product parameters were analyzed. Results: Two hundred procedures (100 per device) were included. The Spectra Optia system showed higher total nucleated cells and MNC collection efficiencies (18.6(10.2‐29.7) vs 7.9(4.1‐14.8)% and 43.6(20.3‐59.5) vs 23.3(11.4‐37.1)%, P < .001) and monocyte and lymphocyte collection efficiencies (55.2(17.7‐83.2) vs 22.8(9‐38.9)% and 38.3(26.7‐53.4) vs 22.2(9‐38.9)%, respectively, P < .001). Absolute platelet loss (PL) and PL per liter of blood processed were significantly lower in the Spectra Optia group (22.9(18.3‐28.1) vs 33.6(26.5‐41.1)%, P < .001 and 3.7(3.1‐4.5) vs 4.3(3.5‐4.2)%, P = .01, respectively). However, granulocyte contamination was higher (4.5(1.3‐36) vs 1.2(0.4‐5.7)%, P < .001) and a higher product haematocrit was obtained with the Spectra Optia (1(0.5‐1.6) vs 0.3(0.2‐0.5)%, P < .001), without an impact on irradiation time. Conclusions: In our study, Spectra Optia proved to be safe and effective in collecting MNC with high yield and purity for ECP in GvHD.